The Correlation Of Body Mass Index With Grip Muscle Strength In Elderly Women - Darmawijaya, IP; Vigneswari, Putu Rara Kumbhara; Daryono, Daryono (Sport and Fitness Journal; Vol 10 No 1 (2022): Volume 10, No. 1, January 2022DO - 10.24843/spj.2022.v10.i01.p03, 2022)
Elderly (elderly) is closely related to problems with the musculoskeletal system. With increasing age, the elderly experience an aging process that will decrease the production of synovial fluid in the joints, decrease muscle tone and decrease muscle strength. One of the decrease in muscle strength is a decrease in hand grip muscle strength. Hand grip muscle strength can be influenced by several factors, one of which is body mass index (BMI). This study was conducted in May 2021 with the aim of knowing the relationship between body mass index and hand grip muscle strength in elderly women aged 60-67 years in Kemoning Village, Klungkung Regency, Bali. The research design used was cross sectional and obtained a sample of 12 people. Hand grip muscle strength was measured using the Hand Grip Dynamometer, while body mass index (BMI) was obtained from the calculation of body weight (kg) height (m²). The results of the study used the Pearson Product Moment correlation test with the value of Sig. (2-tailed) 0.000 and correlation closeness 0.887. This shows that there is a very strong significant correlation between BMI and hand grip muscle strength in elderly women aged 60-67 years. The hand grip muscle strength of the elderly with the thin category is smaller than the normal category.